Mobility of Chinese and Indian Students - Choudaha, Rahul (International Higher Education, 2012)
Many institutions are under pressure to recruit more international undergraduate students to overcome fiscal strains caused by budget cuts. China and India are large source countries, which are expected to show different trends beginning 2015 due to demographic shifts, self-financed students, pace of reforms and campus concerns. Institutions should prepare for these trends without letting fiscal urgency to lose focus on quality, integrity and diversity.